Implementation of Classroom Management in Students’ Perceptions Using Google Translate in Writing Scientific Articles - Roslaini, Roslaini; Budi Nugroho , Setia (Mudir : Jurnal Manajemen Pendidikan, 2023)
Using Google Translate in English learning still has some issues, such as plagiarism, reducing students’ writing skills, and its translation quality. However, according to previous research, students still use Google Translate in their English learning. Even they potentially use it in writing scientific articles. Therefore, this research aims to uncover the empirical evidence of students’ overall perceptions of using Google Translate in writing scientific articles. One hundred English Education students participated in this research. This research uses a survey method and shares the instrument questionnaire modified based on Technology Acceptance Model (TAM). The data collected were analyzed using a descriptive qualitative method. The research findings reveal that students positively perceived using Google Translate in writing scientific articles. This positive perception is predicted through the perceived usefulness, perceived ease of use, attitude, and behavioral intention variable. The findings also reveal that students are proficient enough in using Google Translate to write scientific articles. Nevertheless, the researcher suggested that the students develop their writing skills since it can also be useful in maximizing the result of Google Translate use.